SOP of Information System Security on Koperasi Simpan Pinjam Using ISO/IEC 27002:2013 - Andriana, Myra; Sembiring, Irwan; Hartomo, Kristoko Dwi (Jurnal Transformatika, 2020)
Information security problems always increase every year. One way to minimize problems related to information system security is to establish an SOP. This study was conducted in koperasi simpan pinjam for several reasons that there has never been an assessment related to the level of security of the information system used, there are threatshave occured, and there do not have documented information system security procedures. The SOPs compiled in this study are based on the ISO/IEC 27002:2013 framework. The method used is qualitative with the OCTAVE framework to process the information obtained. Meanwhile, to calculate the value of each risk, FMEA is used. This study shows that 22% of the risks invloved in koperasi simpan pinjam have low categories, 59% medium categories and 19% high categories. The final result of the stiff research is the proposed 8 policies and 12 information system security procedures for koperasi simpan pinjam.